Development and validation of the technology adoption and gratification (TAG) model in assessing lecturers’ ICT use / A.Y.M. Atiquil Islam - A.Y.M., Atiquil Islam (2015)
In this age of exponential knowledge growth, where Information and Communication Technology (ICT) has been playing a dominant role, the authorities of Higher Education concerned have to ensure that the ICT facilities remain within the reach of the lecturers for their teaching and research purposes. However, despite a decade of existence, the ICT facilities were found to be underutilized by lecturers. Constructs such as computer self-efficacy, perceived ease of use, perceived usefulness, use and gratification were hypothesized to be major barriers. In doing so, the prime objective of this study was to develop and validate the Technology Adoption and Gratification (TAG) Model to assess the lecturers’ adoption and gratification in using ICT facilities in higher education. The second purpose of this study was to evaluate the cross-cultural validation of the causal structure of the TAG model. The respondents were collected from two public universities, namely, University of Malaya in Malaysia and Jiaxing University in China. A total of 396 lecturers were selected using a stratified random sampling procedure. A questionnaire consisting of items validated from prior studies were put together and modified to suit the current study. A seven-point Likert scale asking the respondents of the extent of their agreement/disagreement to the items constituting the construct in the questionnaire was used. The questionnaire’s validity and reliability were established through a Rasch model using Winsteps version 3.94. The sample size was judged adequate for the application of Structural Equation Modeling (SEM) to develop and validate the Technology Adoption and Gratification (TAG) Model as well as assess all the research hypotheses. The data was analyzed using AMOS version 18. The findings of the TAG model discovered that computer self-efficacy had a statistically significant direct influence on perceived usefulness and perceived ease of use. Subsequently, lecturers’ perceived ease of use and perceived usefulness had also statistically significant direct influence on their gratification in using ICT facilities in higher education. Moreover, perceived usefulness and perceived ease of use revealed significant direct influence on lecturers’ intention to use ICT facilities for their teaching and research. Similarly, lecturers’ intention to use had statistically significant direct effect on their gratification as well as actual use of ICT facilities, respectively. On the other hand, computer self-efficacy had a significant indirect influence on gratification mediated by perceived ease of use and perceived usefulness, respectively. Meanwhile, computer self-efficacy had also significant indirect influence on lecturers’ intention to use mediated by perceived ease of use and perceived usefulness, respectively. Eventually, lecturers’ perceived ease of use and perceived usefulness had statistically significant indirect influence on their gratification in using ICT facilities in higher education mediated by intention to use. The results of the invariance analysis of the TAG model demonstrated that the model was valid for measuring lecturers’ adoption and gratification in using ICT facilities. However, the TAG model works differently in the cross-cultural settings. The findings contribute to the body of knowledge by developing and validating the TAG Model as proposed in this study. The results will also help the Universities’ higher authority in taking and providing necessary steps towards training to the personnel regarding the application of the ICT facilities in higher education.